Exploring the role of physical activity for health, behaviour, and cognition in children with autism spectrum disorder - Bremer, Emily (My University, 2019)
Children with autism spectrum disorder (ASD) experience difficulties with social communication and social interactions, in addition to the presence of a restricted or repetitive range of behaviours and interests. On top of these core symptoms, children with ASD experience numerous health deficits, as well as impairments in executive functioning. It is possible that physical activity may be an effective intervention to collectively address these deficits and behavioural challenges. Yet, to-date, literature in this area has been limited. Therefore, this dissertation explored the role of physical activity and its relationship to pertinent health, behavioural, and cognitive variables in children with ASD. The first study in this dissertation demonstrated the feasibility and test-retest reliability of select fitness assessments in 7-12 year old children with ASD. Study two demonstrated the association between motor competence and adaptive behaviour. The third study built on this work by showing that motor competence and fitness are positively associated and that adaptive behaviour moderates this relationship. However, significant associations were not present between physical activity and health or behavioural variables. Lastly, study four demonstrated that an acute bout of exercise improves executive functions in children with ASD, with a circuit-based workout eliciting larger effects than aerobic exercise. Collectively, this dissertation provides a comprehensive examination of the role of physical activity for children with ASD. Specifically, these studies highlight the important relationships between motor competence and behaviour, irrespective of physical activity levels, while also highlighting the acute effect of physical activity on executive functions. These findings provide important foundational knowledge that can be built upon to improve the health and behavioural well-being of children with ASD through physical activity-based programs and interventions.